Principles of metabolic surgery - Thomusch, Oliver; Karcz, W. Konrad (Springer Berlin Heidelberg, 2012)
For physicians and surgeons entrusted with the care of patients with morbid obesity and related diseases; also for nurses and other professionals on the team. "Principles of Metabolic Surgery" delivers a succinct account of current knowledge and an excellent overview of modern treatment strategies for morbid obesity. Attractively designed, this user-friendly textbook provides the latest on therapy, monitoring, and management, including: -Completely up-to-date coverage of modern metabolic surgery -Current understanding of the pathophysiology of morbid obesity -Current clinical therapy strategies for conservative and surgical approaches -Recent references In concise, readable chapters, this well-illustrated textbook outlines major concerns and considerations surrounding metabolic surgery. With respect to new insights from basic and clinical research, clear guidelines and practical clinical advice are given to improve the outcome of treatment for morbid obesity.